Synthesis of Carbazole Alkaloids by Ring‐Closing Metathesis and Ring Rearrangement–Aromatization. (19th November 2015) - Dhara, Kalyan; Mandal, Tirtha; Das, Joydeb; Dash, Jyotirmayee
Abstract: Aprocess for the assembly of carbazole alkaloids has been developed on the basis of ring‐closing metathesis (RCM) and ringrearrangement–aromatization (RRA) as the key steps. This method is based on allyl Grignard addition to isatin derivatives to provide smooth access to 2, 2‐diallyl 3‐oxindole derivatives through a 1, 2‐allyl shift. The diallyl derivatives were used as RCM precursors to afford a novel class of spirocyclopentene‐3‐oxindole derivatives, which underwent a novel RRA reaction to afford carbazole derivatives. The synthetic sequence to carbazoles was shortened by combining the RCM and RRA steps in an orthogonal tandem catalytic process. The utility of this methodology was further demonstrated by the straightforward synthesis of carbazole alkaloids, including amukonal derivative, girinimbilol, heptaphylline, and bis(2‐hydroxy‐3‐methylcarbazole). Abstract : Die Addition von Allyl‐Grignard/Indium‐Reagentien an Isatine, Ringschlussmetathese (RCM) und Ringumlagerung‐Aromatisierung (RRA) ergibt Carbazolderivate in hohen Gesamtausbeuten (siehe Schema). Der RCM‐Schritt liefert spirocyclische 3‐Oxindole, die durch säurekatalysierte RRA zu den Carbazolen reagieren. Ein stufenökonomischer RCM/RRA‐Tandemprozess wurde ebenfalls entwickelt und zur Synthese von Carbazol‐Alkaloiden verwendet.